PERAN AYAH DALAM PENDIDIKAN ANAК PADA KELUARGA TKW : THE ROLE OF FATHERS IN CHILDREN'S EDUCATION IN FAMILIES OF MIGRANT WORKERS - Mustofa (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2012)
The social reality of a woman leaving her family to work as a migrant worker abroad has both positive and negative impacts, both for the migrant worker herself and for her family. A woman (wife) cannot fulfill her duties and obligations to her family due to her profession as a migrant worker. Women who work as migrant workers bring new values that are absorbed through the process of cultural acculturation in their host countries, supported by the improved economic position of wives, either directly or indirectly. This situation increases the economic status of families, which in turn increases the economic status of the migrant worker's family. Women who work as TKWs bring new values absorbed through the process of cultural acculturation in their host countries, supported by the improved economic status of wives, which directly or indirectly raises their bargaining position within the family. In other words, from a gender perspective, TKWs have the opportunity to dismantle local gender relations patterns with all their patriarchal hegemony. On the other hand, for families, especially those with wives who are TKWs, the social functions and responsibilities of wives towards their husbands and children are affected. The roles and responsibilities of the family in the form of childcare, care, and education of children should ideally be carried out jointly by the father and mother. However, in families TKW families, this does not occur; family responsibilities related to childcare, maintenance, and education of children become the sole responsibility of the husband or other family members (aunt, uncle, grandmother). Realitas sosial kepergian seorang perempuan menjadi Tenaga Kerja Wanita (TKW) dari tengah keluarga sebagai migran ke luar negeri membawa dampak positif dan negatif, baik bagi TKW secara individu maupun bagi keluarganya. Seorang wanita (istri) tidak bisa menjalankan tugas dan kewajibannya kepada keluarga akibat profesinya sebagai TKW. Perempuan yang berprofesi sebagai TKW membawa nilai-nilai baru yang diserap melalui proses akulturasi budaya di negara perantauannya yang didukung dengan posisi ekonomi isteri yang meningkat secara langsung atau tidak langsung kondisi ini menaikkan posisi tawarnya di tengah keluarga. Dengan kata lain dalam perspektif gender, TKW berpeluang melakukan pembongkaran pola relasi gender lokal dengan segala hegemoni patriarkhi. Di lain pihak bagi keluarga, khususnya yang berstatus sebagai isteri, TKW terkait fungsi dan tanggung jawab sosial istri terhadap suami dan anak. Peran dan tanggung jawab keluarga dalam bentuk pengasuhan, perawatan, maupun pendiddikan anak idealnya dilakukan secara bersama oleh ayah dan ibu. Akan tetapi dalam keluarga TKW hal tersebut tidak terjadi, tanggungjawab keluarga terkait dengan pengasuhan, pemeliharaan dan pendidikan anak menjadi tanggungjawab suamilayah saja atau anggota keluarga lain (bibi, paman, nenek).